Germinação em temperatura sub-ótima de embriões de Inga vera subsp. affinis obtidos sob diferentes condições ambientais - Lamarca, Edmir Vicente; Bonjovani, Marcio Roberto [UNESP]; Faria, José Marcio Rocha; Barbedo, Claudio José (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2013)
Physiological responses like the thermal requirements for germination may be influenced during seed formation by environmental conditions such as water availability and temperature. Here we analyzed germination of embryos of Ingavera subsp. affinis from different sources in response to various temperature regimes, including calculation of degree days and accumulated rainfall during development and maturation. Embryos were taken from ripe fruits collected on trees located in São Paulo and Minas Gerais, and were analyzed as to germination, water content and dry matter content. The results showed that the origin of the embryos was related to variation in response under sub-optimal temperatures. Depending on the origin, I.vera subsp. affinis embryos were able to germinate even at low temperatures (10 to 15 ºC), with better performance attained from 20 to 25 ºC. This variation may be associated, among other factors, to environmental conditions during maturation and to the maturation stage at seed dispersal.

As condições hídricas e térmicas do ambiente durante a formação das sementes podem condicionar diversas respostas fisiológicas, como a exigência térmica para a germinação. Neste trabalho analisou-se a germinação de embriões de Inga vera subsp. affinis de origens distintas em resposta a diferentes temperaturas, incluindo-se o cálculo dos graus-dia e da chuva acumulada durante o desenvolvimento e maturação. Os embriões foram obtidos de frutos maduros de matrizes localizadas em São Paulo e Minas Gerais e analisados quanto ao teor de água, conteúdo de massa seca e germinação. Os resultados demonstram variações nas respostas germinativas entre as origens dos materiais, sob temperatura sub-ótima. Dependendo da origem os embriões de I.vera subsp. affinis germinam a partir de 10 ºC ou 15 ºC e apresentam melhor desempenho em tempo a partir de 20 ºC ou 25 ºC. Tais variações podem estar associadas, entre outros fatores, às condições do ambiente de formação e ao grau de maturidade das sementes no momento da dispersão.
Germination at suboptimal temperature of embryos of Inga vera subsp. affinis produced at different environmental conditions
Keywords: graus-dia; sementes florestais; Leguminosae; degree-day; forest seeds; Leguminosae